2019
DOI: 10.29252/pbp.1.1.42
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effects of isolated Eugenol of Syzygium aromaticum

Abstract: Letter to editor Eugenol (4-allyl-2-methoxy phenol) is a phenolic compound of the clove family Syzygium aromaticum (L.) Merr. & L.M.Perry. In traditional and modern medicine, clove oil has been used as an antimicrobial, antiseptic, antispasmodic, antioxidant, anti-inflammatory, anesthetic, anticarcinogenic, neuroprotective ability, hypolipidemic efficiency, and antidiabetic effect, induce apoptosis by destruction the mitochondrial membrane and production of reactive oxygen species, household products, fragranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The plant has anti-inflammatory, antibacterial, antioxidant, anticancer, analgesic and neuroprotective as well as wound healing effects [25]. Spathulenol, caryophyllene oxide, linalool, alpha-terpineol, trans-caryophyllene and geraniol alpha-phellandrene, beta-myrcene and trans-caryophyllene can be active ingredients of these two plants that have the above-mentioned therapeutic effects [26][27][28][29][30][31][32][33]. Studies have shown that medicinal plants have both traditional and modern research with the use of stand-alone medicinal and therapeutic effects and their beneficial effects through their active ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…The plant has anti-inflammatory, antibacterial, antioxidant, anticancer, analgesic and neuroprotective as well as wound healing effects [25]. Spathulenol, caryophyllene oxide, linalool, alpha-terpineol, trans-caryophyllene and geraniol alpha-phellandrene, beta-myrcene and trans-caryophyllene can be active ingredients of these two plants that have the above-mentioned therapeutic effects [26][27][28][29][30][31][32][33]. Studies have shown that medicinal plants have both traditional and modern research with the use of stand-alone medicinal and therapeutic effects and their beneficial effects through their active ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…Cloves oil contain 70-90% eugenol from several previous studies (14). Eugenol (4-allyl-2methoxyl) is a phenolic compound that can be used for anesthesia (15). Clove itself has been used as an anesthetic material in various commodities, such as fish (13,16,17), shrimp (18), even abalone (19).…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal herbs are used for the treatment of variety of diseases and disorders (1)(2)(3)(4)(5)(6)(7). Herbs exert their effect through the active ingredients and antioxidants available (4)(5)(6)(7)(8)(9)(10). Ziziphus is an important genus of medicinal herbs that is important in traditional medicine.…”
Section: Introductionmentioning
confidence: 99%